Immunogenicity of a novel anti-allergic vaccine based on house dust mite purified allergens and a combination adjuvant in a murine prophylactic model - Ramírez, Wendy; Torralba, Damarys; Bourg, Virgilio; Lastre, Miriam; Perez, Oliver; Jacquet, Alain; Labrada, Alexis (Frontiers in Allergy, 2022)
The outer-membrane-derived proteoliposome (PL) of Neisseria meningitidis has been reported as a potent vaccine adjuvant, inducing a Th1-skewed response. This work aimed to assess the immunogenicity of a novel anti-allergic vaccine candidate based on allergens from Dermatophagoides siboney House Dust Mite and a combination adjuvant containing PL and Alum. In a preventative experimental setting, BALB/c mice were administered with 3 doses containing 2µg of Der s1 and 0.4 µg Der s2 allergen, PL and Alum, at 7 days intervals, by subcutaneous route. Further, mice were subjected to an allergen aerosol challenge for 6 consecutive days. Serum IgE, IgG1, and IgG2a allergen-specific antibodies were assessed by ELISA. Cytokine levels in supernatants of D. siboney stimulated lymphocyte cultures and in broncho-alveolar lavage (BAL) were measured by ELISA. Lung tissues were subjected to histological examination. The vaccine prevented the development of both, systemic (IgE) and local allergic responses (featuring lower IL-4, and IL-5 levels in BAL) upon allergen exposure by the inhalant route. Histological examination showed also a diminished allergic inflammatory response in the lungs. After the allergen challenge, cytokine levels in stimulated lymphocyte cultures showed lower values of IL-13 and augmented IFN- and IL-10. The vaccine induced a mixed IgG2a/IgG1 antibody response; although only IgG2a was PL-dependent. Both, IgG1/IgE and IgG2a/IgE ratios showed significantly greater values in vaccinated mice. The findings support a preventative anti-allergic effect associated with the induction of a Th1-like IFN-/IL-10 response. IgG1/IgE and IgG2a/IgE ratios could be useful biomarkers for translation into clinical trials.